2021
DOI: 10.1080/23276665.2020.1866624
|View full text |Cite
|
Sign up to set email alerts
|

Advancing international cooperation as a strategy for managing pandemics

Abstract: The COVID-19 pandemic has fractured international relationships and challenged governments to adapt in new and unprecedented ways. This crisis has caused many governments to look inward and avoid a globalised response. However, using the case study of South Korea, the author argues that a more open approach and international collaboration are needed to tackle COVID-19 and to avert a future pandemic crisis. Relying on the policy innovation and policy transfer literature, this article suggests how countries can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Certain personality disorders enhance the likelihood of loneliness, anxiety, and depression (Hardin et al, 2021), and the most severe of these is the dark triad (Kowalski, 2001). Recently, it has been observed that individuals with the dark triad have had issues obeying government regulations (Nowak et al, 2020;Zajenkowski et al, 2020;You, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain personality disorders enhance the likelihood of loneliness, anxiety, and depression (Hardin et al, 2021), and the most severe of these is the dark triad (Kowalski, 2001). Recently, it has been observed that individuals with the dark triad have had issues obeying government regulations (Nowak et al, 2020;Zajenkowski et al, 2020;You, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Certain personality disorders enhance the likelihood of loneliness, anxiety, and depression (Hardin et al, 2021 ), and the most severe of these is the dark triad (Kowalski, 2001 ). Recently, it has been observed that individuals with the dark triad have had issues obeying government regulations (Nowak et al, 2020 ; Zajenkowski et al, 2020 ; You, 2021 ). While research showed that for battling sensations of being lonely and random dark moods individuals are increasingly employing autonomous sensory meridian response (ASMR) stuff to relax and alleviate anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%